Electrochemical reduction of graphene oxide and its in situ spectroelectrochemical characterization - Kauppila, Jussi (2013)
The electrochemical properties of self-assembled films of graphene oxide (GO) on mercaptoethylamine (MEA) modified rough Au-surfaces were studied. The film deposition process on MEA primed gold was followed by surface plasmon resonance measurements and the film morphology on 3-aminopropyltriethoxysilane primed Si(100)-surface was studied by atomic force microscopy. The deposited few layer thick GO films on gold were electrochemically reduced by cyclic voltammetry simultaneously as the structural changes in the film were recorded by in situ vibrational spectroscopies. In situ surface enhanced infrared spectroscopy results indicate that the effect of the applied potential on the GO structure could be divided into two parts where the changes occurring at moderate negative potentials are mainly related to changes in the double layer at the film–electrolyte interface and to hydrogen bonding of intercalated water between the GO sheets. At potentials more negative than −0.8 V vs. Ag/AgCl the reduction of GO starts to take place with concomitant conversion of the different functional groups of the film.